Mirrored Disembodied Spirits: Daphne du Maurier and Frenchman’s Creek’s Dona St Columb - de la Morena Recio, Andrea (Journal of Artistic Creation and Literary Research, 2025)
Frenchman’s Creek (1941), a thrilling read as a pirate novel, contains deeper meanings underneath the surface of the text. In order to create a pirate story with a female warrior as the heroine, Daphne du Maurier utilizes her own desires, anxieties, and love of pirate stories. This paper reconsiders, via the frameworks of queer studies and feminism, the impact of Daphne du Maurier’s personal life and identity on the character of Dona, the protagonist of the novel.